Trend of Dairy Population an Milk Production in Boyolali, Central Java, Indonesia - Hidayah, Nurulia (2015)
This study is one part of the business development strategy research of dairy cattle in Boyolali, Central Java. This study aimed to analyze the trend of the population of dairy cattle and milk production in Boyolali, Central Java. This study was conducted between November 2010 until January 2011 in the district of Boyolali by using the survey method. Total respondents were used in this study were 266 farmers. Primary data was collected by interviews based on a questionnaire that has been prepared. Secondary data were obtained from the Central Bureau of Statistics, Department of Animal Husbandry and Fisheries, and local governments Boyolali. The average of dairy lactation ownership is 6.40 AU. The average production of cow's milk in Boyolali is still low at 8 liters/head/day. Trend dairy cow population is Y=4,7182e0,0063x, production trend equation is Y=5.8567 e0,0052x. Both equations are used to estimate the size of the population of dairy cattle and milk production in the coming years. Trend population of dairy cows, milk production is increasing every year.